Answer:
7
Step-by-step explanation:
First you multiple 8x times 7x and get 56x and since 3y doesn't have another y so u Leave tht as 3y then you multiply 3z times 6z and get 18z then you multiply 4 times 6 and get 24 (56x^3y)(18z^24)
x-3y=7 2x-6y=12
You can multiply -2 in the first equation like this.
x+6y=7
2x-6y=12
Now you can eliminate 6y and -6y so cross them out and do x-2 which is -1 and 7-12 which is -5 -1/-5 would be .2
<h3 />
False because if it’s a positive number then the opposite is gonna be a negative
Answer:
From what I can comprehend I believe the answer is <em>3.2x + -4</em>
Step-by-step explanation:
0.4(2x-9) = 0.8x - 9
0.8x - 9 - 0.6(4x+5)=
0.8x - 9 + 2.4x+5
0.8+2.4 = 3.2x
-9 + 5 = -4
3.2x + -4